Students\' Viewpoints on Advisors\' Nonverbal Communication Skills: A survey in Schools of Health and Allied Health Sciences in Kashan University of Medical Sciences - Mohammad Sabbahi Bigdeli; Mahhamadreza Afazel; Seid Hamidreza Sayedi Arani; Fakhrosadat Mirhosseini; Somayeh Shahri (مجله ایرانی آموزش در علوم پزشکی, 2012)
Introduction: One of the most important principles of counseling is proper use of communication skills nonverbal communication is one of the most effective ways of available communications. This research has been performed to study students' viewpoints on advisors’ nonverbal communication skills in schools of health and allied health sciences of Kashan University of Medical Sciences. Methods: In a descriptive cross-sectional study, 202 students of schools of health and allied health sciences of Kashan University of Medical Sciences were asked about their viewpoints toward advisors’ nonverbal communication skills. Students were selected through stratified random sampling. A self-made questionnaire was used to assess nonverbal communication skills considering five dimensions through 39 statements. Students' satisfactions with advisors were evaluated by a separate question. Validity of the questionnaire was confirmed via content validity, and its reliability was confirmed using Cronbach’s Alpha (α=0.96). Data was analyzed using descriptive statistic and nonparametric inferential tests (Mann Whitney, Kruskal-Wallis, Friedman, and Spearman correlation test). Results: The total score of nonverbal communication skills of thesis supervisors was 3.39±0.71 ( out of 5). The highest means belonged to “advisors’ appearance” (3.76±1.10) and “their facial expression during consulting” (3.54±1.07). The score of students’ satisfaction with advisors was 3.36±1.28 accordingly. Spearman test showed a significant correlation between students' satisfaction with advisors performance and the five dimensions of nonverbal communication skills (α>0.05). Conclusion: According to the results, the level of nonverbal communication skills and students' satisfaction with advisors were moderate. It seems necessary for faculties under investigation to develop effective strategies to promote their communication skills. This could increase the level of satisfaction among students and improve the quality of counseling sessions.